Refining and Assessing Gender-Tailored Group Therapy for Veteran Men With Military Sexual Trauma: Protocol for a Mixed Methods Study - Jonathan Yahalom; Erin P Finley; Sheila O'Brien; Brandon C Yarns; Lindsey L Monteith; Ariel J Lang; Alison B Hamilton (JMIR Research Protocols, 2026)
Abstract Background Military sexual trauma (MST) among veteran men is common, underreported, and associated with substantial psychological morbidity. Despite evidence that gender-related distress and shame pertaining to masculinity contribute to treatment avoidance and dropout, MST interventions within the US Department of Veterans Affairs have not been developed specifically for men. Objective The objective of this study is to develop a gender-tailored group psychotherapy for veteran men with histories of MST. Guided by implementation science frameworks, the mixed methods study described in this paper proposes to iteratively refine the previously implemented Men’s MST Group (MMG), a 12-session, gender-tailored, trauma-focused group intervention that integrates dynamic group processes, mindfulness-informed distress tolerance, and psychoeducation. Methods We draw on a synthesis of the intervention mapping framework and the access reconceptualization model to identify patient and system characteristics that contribute to treatment access and engagement. For aim 1, we will refine MMG through focus groups, qualitative interviews, and expert consultation. For aim 2, we will pilot-test MMG in a randomized controlled trial (n=32) comparing MMG to present-centered group therapy. For aim 3, we will evaluate implementation barriers and facilitators and iteratively refine the intervention through posttreatment qualitative interviews and expert panel review. Results This study was funded with a start date of January 2025 and is anticipated to end in December 2029. As of July 2026, we have completed data collection for aim 1 and are currently analyzing data from 31 semistructured interviews. As of July 2026, we are also refining the MMG treatment protocol, which we plan to implement in a pilot randomized controlled trial in January 2027. Results of aim 1 are anticipated to be published in 2027. Participant recruitment for the aim 2 pilot trials has not begun. Conclusions The goal of the current project is to refine and pilot-test a gender-tailored group psychotherapy for veteran men with histories of MST. We anticipate that the intervention will demonstrate feasibility, acceptability, and implementation potential because it was developed through an iterative process incorporating feedback from veterans, clinicians, and subject matter experts. Should study objectives be met, the next step will be to conduct a fully powered randomized controlled multisite trial. We additionally plan to disseminate findings regarding treatment needs, preferences, and barriers to care among men with histories of MST, which may inform future treatment development and implementation efforts beyond the current project.